Sequence varieties in potato virus y isolated from song Hong river delta provinces - Van, Pham Thi; Hung, Nguyen Minh; Binh, Le Tran; Ha, Chu Hoang (Academia Journal of Biology, 2012)
Potato virus Y (PVY) is one of the most common and destructive viruses found in potato. The virus is the type-member of the Potyvirus genus, which the largest among the plant virus groups. This virus is characterized by flexuous particles containing a 10 kb positive-sense RNA. Characterization of newly emerged recombinant strain variants has included analysis of nucleic acid data, enabling development of new detection assays, often based on RT-PCR techniques. In this work, we used the RT-PCR techniques to analyze genetic diversity of PVY on potato which were collected from Song Hong river delta provinces (Hanoi - HN, Nam Dinh - ND and Thai Binh - TB) by cloning, sequencing and analyzing coat protein (CP) coding gene. Three sequences of the CP gene with the length of 801 bps have been registered in GenBank as accession AM411504 for Hanoi isolate, AM411503 for Nam Dinh isolate and AM411502 for Thai Binh isolate. The identities of three isolates together in nucleotide and amino acid level are 91.3-99.1% and 93.6-98.9%, respectively. On the basis of sequence identity and phylogenetic analysis of nucleotide sequence and deduced amino acid sequence of CP revealed that HN and ND isolates belong to PVYNTN and TB isolate belongs to PVYO.